DUI mode learning and barriers to innovation - the case of Germany - Jörg Thomä (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2017)
This paper aims to provide a better understanding of informal modes of learning based on Doing, Using and Interacting (DUI). Innovating firms from Germany are grouped according to the degree to which they combine DUI mode competencies with formal learning of science and technology (i.e. the Science, Technology and Innovation – STI – mode). To more deeply assess the practical relevance of this grouping for innovation policy, it is subsequently examined how a firm's learning mode relates to the relevance of different sets of innovation barriers. According to the empirical results, DUI mode learning is generally important in the field of innovation, since it occurs either in its pure form or in combination with formal processes of research and development (R&D). Moreover, the more dominant that the DUI mode of learning is at the company level, the more likely that the corresponding firm is small. In such a less R&D-oriented knowledge environment, innovating firms can exploit certain competitive advantages when they concentrate on their experience-based DUI mode competencies. On the other hand, firms trying to compensate for limited in-house R&D capabilities through collaboration with external partners have to overcome a number of knowledge and market barriers to innovation. The paper concludes with implications for policy and research.
Keywords: O31; O38; 330; Modes of learning; Barriers to innovation; Innovation without R&D; Small firms; Nontechnological innovation; Vocational education